Do reputable issuers provide better-quality securitizations? - Solomon Y. Deku; Alper Kara; David Marqués Ibá\~nez (European Central Bank (ECB), 2019)
We examine the link between issuer reputation and mortgage-backed security (MBS) performance using a sample of 4,247 European MBS issued between 1999 and 2007. We measure performance with credit rating downgrades and delinquencies and track their changes over the long term. We find that, overall, MBS sold by reputable issuers are collateralised by higher quality asset pools which have lower delinquency rates and are less likely to be downgraded. However, as credit standards declined during the boom period of 2005-2007, asset pools securitized by reputable issuers were of worse quality compared to those securitized by less reputable issuers. Therefore, reputation as a self-disciplining mechanism failed to incentivise the production of high quality securities during the credit boom.
Keywords: G21; G24; G28; 330; Mortgage-backed securities; issuer reputation; rating shopping